2018
DOI: 10.1093/neuros/nyy045
|View full text |Cite
|
Sign up to set email alerts
|

White Blood Cell Count Improves Prediction of Delayed Cerebral Ischemia Following Aneurysmal Subarachnoid Hemorrhage

Abstract: Good-grade patients with early elevations in WBC count have a similar risk and hazard for DCI as poor-grade patients. Good-grade patients without elevated WBC may be candidates to be safely downgraded from the intensive care unit, leading to cost savings for both patient families and hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 36 publications
1
37
0
Order By: Relevance
“…Collected data included patient characteristics on admission and during treatment course, radiological features, and clinical outcomes. SAH and the radiological severity were evaluated using the WFNS grading scale (15) and Fisher score, respectively. The incidence of cerebral vasospasm, acute hydrocephalus, and delayed cerebral ischemia (DCI) were also obtained for each patient.…”
Section: Methodsmentioning
confidence: 99%
“…Collected data included patient characteristics on admission and during treatment course, radiological features, and clinical outcomes. SAH and the radiological severity were evaluated using the WFNS grading scale (15) and Fisher score, respectively. The incidence of cerebral vasospasm, acute hydrocephalus, and delayed cerebral ischemia (DCI) were also obtained for each patient.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike ICH, there are abundant prospective human data in SAH to suggest elevated circulating leukocyte is associated with poor outcome and SAH complications [97][98][99][100][101] (Table 3). Across studies, early increase in blood leucocytes predicted delayed cerebral ischemia (DCI) and poor SAH outcome, while its association with cerebral vasospasm was inconsistent.…”
Section: Peripheral Immune Cells and Hemorrhagic Strokementioning
confidence: 99%
“…5,[28][29][30][31][32] aSAH can induce the leukocytosis and increased neutrophils by stimulating the systemic cellular responses that can cause the brain injury and delayed cerebral ischemia. 33,34 Early studies showed that the growth and rupture of cerebral aneurysms were promoted via the leukocyte infiltration and inflammatory reaction in the wall of aneurysms. [35][36][37][38] The results of histopathology found that the thinned wall of aneurysms was related to leukocytosis.…”
Section: F I G U R E 2 Roc Curve Of the Prognosis In Patients With Aashmentioning
confidence: 99%